2005
DOI: 10.1007/s11244-005-3813-5
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for the Preparation of Multiply Substituted Cyclopentadienes and Related Compounds

Abstract: Substituents on cyclopentadienyl ligands significantly influence the reactivity and catalytic efficiency of their transition metal complexes. Therefore, development of synthetic methods for cyclopentadiene derivatives possessing different substituents has been in great demand. In this paper, we report new synthetic methods for multiply substituted cyclopentadienes recently developed in this group. In principle, three types of preparative methods are described. Firstly, zirconacyclopentadienes in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…8,9 Moreover, feasible and practical synthesis of multi-substituted cyclopentadienes is quite limited due to the use of complex substrates and/or expensive transition metals. 10,[21][22][23][24][25][26][27][28][29] We have reported one-step synthesis of multisubstituted cyclopentadienes from 3-alkoxycarbonylallylidenephosphorane and α-halocarbonyl compounds via [3 + 2] annulation under mild conditions. [30][31][32] This convenient method has been employed by Takahashi and Onitsuka et al to construct various chiral Cp′-Fe(II), -Rh(I), and -Ru(II) complexes which have been demonstrated to be effective catalysts for a series of enantioselective reactions.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, feasible and practical synthesis of multi-substituted cyclopentadienes is quite limited due to the use of complex substrates and/or expensive transition metals. 10,[21][22][23][24][25][26][27][28][29] We have reported one-step synthesis of multisubstituted cyclopentadienes from 3-alkoxycarbonylallylidenephosphorane and α-halocarbonyl compounds via [3 + 2] annulation under mild conditions. [30][31][32] This convenient method has been employed by Takahashi and Onitsuka et al to construct various chiral Cp′-Fe(II), -Rh(I), and -Ru(II) complexes which have been demonstrated to be effective catalysts for a series of enantioselective reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopentadienes of this type, otherwise difficult to prepare, might be expected to have applications as building units for conjugated organic materials. [15,16] In addition to acyl chlorides, we also treated these dilithiodienes with esters and anhydrides. The results showed that the reactions between dilithiodienes such as 1a-c and esters such as PhCO 2 Me, PhCO 2 Et, and AcOEt generally afforded mixtures of products, probably because of further reactions of the intermediates generated in situ.…”
Section: Introductionmentioning
confidence: 99%
“…The current reaction represents a novel and facile synthetic route to useful cyclopentadienes , with a quaternary carbon atom. We then moved to the optimization of reaction parameters, such as solvents, bases, and reagent loadings .…”
mentioning
confidence: 99%
“…Cyclopentadiene is a useful type of feedstock and has been widely employed in a variety of transformations . Our current reaction also provides a new approach for the synthesis of cyclopentadiene derivatives, and the products can be readily converted into other useful compounds as shown in Scheme . Hydrogenation of the products gave the substituted cyclopentane 16 in 94% yield.…”
mentioning
confidence: 99%